Inspire Challenge Award: Using IVR to connect farmers to market - CGIAR Platform for Big Data in Agriculture (2018)
Implemented a crowdsourced IVR marketing service to increase linkages between individuals in the value chain. Farmers could report their harvest/needed services through their phone and onto a web platform/App that buyers can use to locate produce. This service completed human centered design studies and prepared for national launch in Nepal.